Evaluation Information System Using UTAUT (Case Study : UMS Vocational School) - Nendy Akbar Rozaq Rais; Muqorobin Muqorobin (Institut Teknologi Bisnis AAS Indonesia, 2020)
Abstract—This admissions study evaluates users and the use of models for the Vocational School information system at the Muhammadiyah University of Surakarta with the UTAUT model by Venkatesh (2003) which has been modified by adding the System Service and Information Quality variables. The respondents are 100 students. From the results of the F and T tests, it is concluded that the variables Performance Expectance, Effort Expectance, Social Influence, System Service and Information Quality have an influence on Behavioral Intention, but only Social Influence and System Service variables have a significant partial effect on Behavioral Intention. In addition, another result is the variable Facilitating Condition and Behaviural Intention simultaneously affect Behavioral Usage. Validity, reliability and assumptions of classical test data show value as a measure of this analysis.